Implementasi Media Digital Interaktif Berbasis Wordwall guna Melatih Maharah Istima’ Peserta Didik Kelas VII H MTsN 1 Lamongan - Fadhilah, Alfina Nur; Syarifah, Ainun (Ta'limi | Journal of Arabic Education and Arabic Studies, 2026)
Listening skills (maharah istima’) in Arabic language learning at the junior secondary level often face challenges due to the use of non-interactive and conventional teaching media, which result in low student motivation. At MTsN 1 Lamongan, students’ listening proficiency remains limited because learning activities tend to rely on traditional methods and static materials. Meanwhile, digital media such as Wordwall offer interactive features and audio-based exercises that can create a more engaging learning environment. This study aims to evaluate the implementation of Wordwall-based interactive digital media in improving the listening skills of seventh-grade students at MTsN 1 Lamongan. Using a descriptive qualitative approach, data were collected through observations, interviews, listening tests, and documentation. The findings indicate that Wordwall successfully increased student engagement and motivation. Interactive exercises—such as audio-based multiple-choice questions and matching games—helped students better comprehend listening materials. However, several challenges emerged, including unclear audio quality and unstable internet connectivity. Overall, the study concludes that Wordwall is an effective tool for enhancing listening skills, provided that technical limitations are adequately addressed. These findings support the use of Wordwall as an innovative alternative learning medium in the digital era.